Electroacupuncture Alleviates Hyperalgesia and Anxiety-Like Behaviors in Pain Memory Model Rats Through Activation of GABAergic Neurons and GABA Receptor in the Rostral Anterior Cingulate Cortex - Jing Sun; Chi Zhang; Yifang Wang; Siqi Xiao; Haiju Sun; Zhiyuan Bian; Zui Shen; Xiaofen He; Jianqiao Fang; Xiaomei Shao (Molecular Neurobiology, 2024)
Recent studies have confirmed that pain memory is often accompanied by negative emotions. Electroacupuncture (EA) can block the retrieval of painful memories, thereby alleviating the associated negative behaviors. However, the underlying mechanism is poorly understood. This study revealed that the effect of EA on pain memory-induced negative behaviors is related to the mediation of GABAergic neuron activity and GABA receptor expression in the rostral anterior cingulate cortex (rACC). Previous studies have shown that the rACC is a crucial area for regulating nociceptive behaviors and negative emotions in pain memory models. The GABAergic neurons and receptors in the rACC are largely involved in pain sensation and related effects. However, the relationships among pain memory, GABAergic neurons and receptors in the rACC have not been investigated. In this study, we established a pain memory model via secondary plantar cross-injection of carrageenan and EA treatment. Using chemogenetic methods and behavioral assessments of pain and negative emotion, we found that early excitation of GABAergic neurons in the rACC blocked the recall of pain memories and reduced anxiety-like behaviors in pain memory model rats. Furthermore, pharmacological methods revealed that excitation of GABA A and GABA B receptors in the rACC blocks hyperpathia associated with pain memory and pain-induced anxiety-like behaviors, while inhibition of GABA A and GABA B receptors reverses these effects. These results suggest that EA may alleviate pain and associated anxiety-like behaviors related to pain memories through the activation of GABAergic neurons and excitation of GABA A and GABA B receptors in the rACC.